Vagal schwannomas of the head and neck: A comprehensive review and a novel approach to preserving vocal cord innervation and function. Issue 7 (7th April 2019) - Sandler, Mykayla L.; Sims, John R.; Sinclair, Catherine; Sharif, Kayvon F.; Ho, Rebecca; Yue, Lauren E.; Téllez, Maria J.; Ulkatan, Sedat; Khorsandi, Azita S.; Brandwein‐Weber, Margaret; Urken, Mark L.
Abstract: Background: Schwannomas, benign tumors arising from neurolemmocytes, are the most common type of peripheral nerve tumors. Extracranial schwannomas are most often found in the parapharyngeal space, commonly involving the vagus nerve to cervical sympathetic trunk. Vagal schwannomas present several unique clinical and therapeutic challenges. Methods: A comprehensive literature review was conducted on 197 articles reporting 235 cases of cervical vagal schwannomas. Presenting symptoms, treatment approach, and postoperative outcomes were recorded and analyzed. Results: Vagal schwannomas commonly present as asymptomatic neck masses. When they become symptomatic, surgical resection is the standard of care. Gross total resection is associated with higher postoperative morbidity compared to subtotal resection. Initial reports using intraoperative nerve monitoring have shown improved nerve preservation. Recurrence rates are low. Conclusion: The combination of intermittent nerve mapping with novel continuous vagal nerve monitoring techniques may reduce postoperative morbidity and could represent the future standard of care for vagal schwannoma treatment.